Uncle Fred in the Springtime - Wodehouse, P. G. (London Arrow Books, 2008)
Uncle Fred is urged by Lord Emsworth to save his prize pig, the Empress of Blandings, from the enforced slimming cure of the haughty Duke of Dunstable.
English Fiction.
Keywords: Nobility -- England--Shropshire -- Great Britain -- England